The Dorset culture longhouse at Brooman Point, Nunavut - Park, Robert (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis paper presents a brief description of a Late Dorset culture longhouse structure and its associated hearth rows located at the Brooman Point site. Following a description of the spatial distribution of finds recovered through the excavation of the longhouse, the paper explores the significance of the architectural and artifactual patterning seen at Brooman Point and other longhouse sites. It is argued that the concept of linearity underlies the Dorset use of these sites. Futhermore, both the range of activities carried out at these sites, and the size of the groups who aggregated at them, may be smaller than is often assumed.